Reasons and countermeasures of nursing disputes in the nucleic acid testing clinic (核酸检测门诊护理纠纷的原因与对策研究) - ZHAO Jialu (赵佳璐); WANG Huaxin (王华新); ZHOU Jie (周洁); TANG Ling (唐玲); MA Kexin (马可欣); ZENG Chunfeng (曾春凤) (中西医结合护理)
Objective To investigate the factors of high incidence of nursing disputes in the nucleic acid testing clinic, and to optimize management and reduce the incidence of nursing disputes. Methods A retrospective before-after study was conducted. Potential reasons of nursing disputes happened between April and September 2021 were retrospectively analyzed, and countermeasures were carried out to optimize management in the nucleic acid testing clinic. The incidence of nursing disputes happened between October 2021 and January 2022 was calculated. Results Issues related to patients, nurses and working environment were main factors causing nursing disputes. The incidence of nursing disputes had decreased from2. 35 to 1. 56 after implementation of optimal management strategy. Conclusion In order to reduce the incidence of nursing disputes and improve the nursing quality in the nucleic acid testing clinic, it is required to enhance the nursing staff’s sense of responsibility and effective communication with patients, standardize the nursing operation process, strengthen cooperation between various departments and improve the hospital workplace environment. (目的 查找导致医院核酸检测门诊护理纠纷发生率高的原因, 通过优化管理降低护理纠纷发生率。方法 本研究采用回顾性自身前后对照方法, 收集2021年4月—9月护理纠纷案例, 分析原因并提出改进措施, 优化核酸检测门诊护理管理质量。统计2021年10月—2022年1月护理纠纷发生率。结果 引起护理纠纷的因素包括患者因素、护士因素、环境因素三个方面。优化核酸检测门诊护理管理后, 护理纠纷事件发生率由实施前的2. 35降低至1. 56。结论 核酸检测门诊护理相关工作人员需要增强自身责任心, 规范自身操作, 积极与患者进行有效沟通; 同时医院还需要加强各部门合作, 改善就诊环境等。通过科学的管理, 可有效减少护理纠纷的发生, 提高患者满意度和护理质量。)